Molecular dynamic simulation of diamond/silicon interfacial thermal conductance - Khosravian, N. (2014)
Non-equilibrium molecular dynamic simulation was employed to investigate the interfacial thermal conductance between diamond and silicon substrate. The interfacial thermal conductance was computed based on Fourier's law. The simulation was done at different temperature ranges and results show that the interfacial thermal conductance between diamond-silicon is proportional to temperature and increases with temperature even above Debye temperature of silicon. Enhancement of thermal boundary conductance with temperature is attributed to inelastic phonon-phonon scattering at the interface. The system size dependence of interfacial thermal conductance was also examined. We found that thermal transport is a function of the system size when the size of system is smaller than the phonon mean free path and increases with the size of structure. We also simulated the effect of interface defect on phonon scattering and subsequently thermal conductance. The results also show that interface defect enhances acoustic phonon scattering which results in reduction of thermal boundary conductance. Our findings provide accurate and valuable information on phonon transport in diamond-silicon structure.